1988
DOI: 10.1161/01.cir.77.3.625
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic mechanisms governing hemodynamic responses to positive inotropic therapy in patients with dilated cardiomyopathy.

Abstract: Clinical trials in patients with dilated cardiomyopathy (DCM) have shown a wide disparity in the hemodynamic responses to positive inotropic therapy. In addition, the response of the failing left ventricle to positive inotropic agents reflects the net interaction of multiple factors, including the magnitude of contractile abnormality and compensatory mechanisms. In the current study, left ventricular geometry, loading conditions, and contractile state were assessed in 13 patients with nonischemic DCM with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
2

Year Published

1992
1992
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(29 citation statements)
references
References 50 publications
(3 reference statements)
0
27
0
2
Order By: Relevance
“…Thus, surgical and medical therapies can be tailored and targeted against each one of these components 13, 14, 15, 16, 24, 25…”
Section: Discussionmentioning
confidence: 99%
“…Thus, surgical and medical therapies can be tailored and targeted against each one of these components 13, 14, 15, 16, 24, 25…”
Section: Discussionmentioning
confidence: 99%
“…LV shape was assessed by computation of end-diastolic and end-systolic sphericity indexes, ie, the ratio of the major to the minor axis at end diastole and end systole. 20 The size of the mitral annulus and the distance separating the plane of the mitral annulus plane from the coaptation between the mitral leaflets at end systole was also measured. 21 The presence and magnitude of MR were assessed by use of the regurgitant color jet over left atrium area method.…”
Section: Gas Exchange Analysismentioning
confidence: 99%
“…The SOLVD investigators, in a placebo-controlled trial of symptomatic heart failure patients, also demonstrated a survival benefit with enalapril treatment of 16% risk reduction, although approximately one third of patients in the active treatment arm had stopped enalapril by the end of the study.21 Importantly, these investigators demonstrated a parallel benefit on frequency of hospitalization for worsening heart failure and a survival benefit largely attributable to a reduction in progressive heart failure in patients with low ejection fractions. Approximately 1 year later, the SOLVD investigators reported on the prevention arm of their study, which examined in a placebo-controlled fashion the effects of enalapril on patients with functional class I or II heart failure and left ventricular ejection fractions of 535% who were not receiving drug treatment for heart failure.75 Although no significant reduction in mortality was seen over the average follow-up of 37 months, there was a 20% reduction in hospitalization for new or worsening heart failure in enalapril-treated patients that was most pronounced among patients with the lowest ejection fractions. An unexpected and interesting finding from the SOLVD study was that on composite analysis of both treatment and prevention arms, enalapril reduced the frequency of both myocardial infarction (23%) and unstable angina (20%).…”
mentioning
confidence: 99%